Instrumen Literasi Numerasi Berbasis Kemampuan Berpikir Komputasi pada Matematika SMP: Pembuktian Validitas Isi dengan Aiken’s. - Zafrullah, Zafrullah; Gunawan, Resky Nuralisa; Ramadana, Nurfitri; Era Mutiara; Nur, Muhammad Imran (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to prove the content validity of a numeracy literacy instrument based on computational thinking skills using Aiken's method. There are five questions divided into nine parts, all of which focus on the material “Algebraic Forms”, ​​and have been validated by five validators from two leading universities. The data analysis technique applied is the Aiken's method, which is used to assess the extent to which this instrument meets the validity criteria. The results of the analysis show that most of the questions in the instrument received good validity scores, with an average validity of 0.81. This score indicates that this instrument is relevant and effective for measuring students' abilities in numeracy literacy and computational thinking. Apart from that, input from validators regarding the use of simpler language for grade 8 students is very valuable and is expected to improve students' understanding of the questions given. It is hoped that these results can contribute to the development of higher quality educational evaluation instruments, as well as being the basis for further research involving instrument testing to prove construct validity and reliability in the context of mathematics learning